Coping Profiles and Differences in Psychological Distress and Quality of Life in Clients Undergoing Assisted Reproductive Techniques: A Latent Profile Analysis - Bai J; Zheng J; Guo N; Dong Y; Wang K; Cheng C; Jiang H; Qian L (Journal of Multidisciplinary Healthcare, 2024)
Jie Bai,1 Jinxia Zheng,1 Nafei Guo,2 Yueyan Dong,1 Ke Wang,1 Cheng Cheng,3 Hui Jiang,2 Lin Qian4 1Shanghai Key Laboratory of Maternal-Fetal Medicine, Shanghai Institute of Maternal-Fetal Medicine and Gynecologic Oncology, Shanghai First Maternity and Infant Hospital, School of Medicine, Tongji University, Shanghai, People’s Republic of China; 2Nursing Department, Shanghai First Maternity and Infant Hospital, School of Medicine, Tongji University, Shanghai, People’s Republic of China; 3School of Nursing, Fudan University, Shanghai, People’s Republic of China; 4Nursing Department, Shanghai East Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of ChinaCorrespondence: Hui Jiang, Nursing Department, Shanghai First Maternity and Infant Hospital, School of Medicine, Tongji University, Shanghai, People’s Republic of China, Tel/Fax +86 21-20261221, Email jianghuitest@163.com Lin Qian, Nursing Department, Shanghai East Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of China, Email lc699536@126.comPurpose: Receiving assisted reproductive technology is stressful due to its long-lasting process, which might pose negative impacts on clients’ psychological well-being and quality of life. This study was to investigate coping profiles among couples undergoing assisted reproductive technology and examine their associations with psychological distress and quality of life.Methods: This cross-sectional study was conducted at the IVF center of a specialized hospital in Shanghai, China. Of 502 eligible clients completed a structured, online survey of socio-demographic information, Dyadic Coping Inventory, Kessler Psychological Stress Scale, and Fertility quality of life. Coping profiles were identified using latent profile analysis and differences between identified profiles on psychological distress and quality of life were examined using analyses of covariance.Results: A three-profile solution was supported: low dyadic coping group (n = 168, 33.50%), moderate dyadic coping group (n = 241, 48.00%), and high dyadic coping group (n = 93, 18.50%). Significant differences between those groups were found in psychological distress and quality of life.Conclusion: The findings of this study have revealed dyadic coping profiles in clients undergoing assisted reproductive technology, which are differentially associated with psychological distress and quality of life.Keywords: assisted reproductive technology, coping, latent profile analysis, psychological distress, quality of life